Nutrition intervention for an international-standard female football player - Robinson, S. L.; Morton, J. P.; Close, G. L.; Flower, D.; Bannock, L. (Journal of Applied Case Studies in Sport and Exercise Sciences, 2014)
Participation in women`s football is rapidly increasing, with more elite players employed on a professional or semi-professional basis than ever before. Despite a wealth of evidence showing an important role for nutrition in football, nutritional methods to improve parameters of performance in the women`s game are sparse, with much of this information extrapolated from the male game. This article provides a cas